2017
DOI: 10.1111/os.12321
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAH19 Modulates Wnt/β‐catenin Signaling by Targeting Dkk4 in Hindlimb Unloaded Rat

Abstract: Our findings demonstrated that low expression of H19, induced by mechanical unloading, leads to development of DOP through inhibition of Wnt signaling by promoting Dkk4 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…[24][25][26][27] Importantly, although the roles of lncRNAs in the process of osteogenesis have been widely reported, [28][29][30] only a few studies have shown that lncRNAs are involved in the occurrence and development of unloading-induced bone loss. 31,32 In the present study, we found that lncRNA OGRU is downregulated during unloading and upregulated during osteoblast differentiation. OGRU overexpression promoted osteoblast activity and matrix mineralization under normal loading and attenuated the suppression of MC3T3-E1 cell differentiation by unloading conditions in vitro.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…[24][25][26][27] Importantly, although the roles of lncRNAs in the process of osteogenesis have been widely reported, [28][29][30] only a few studies have shown that lncRNAs are involved in the occurrence and development of unloading-induced bone loss. 31,32 In the present study, we found that lncRNA OGRU is downregulated during unloading and upregulated during osteoblast differentiation. OGRU overexpression promoted osteoblast activity and matrix mineralization under normal loading and attenuated the suppression of MC3T3-E1 cell differentiation by unloading conditions in vitro.…”
Section: Introductionsupporting
confidence: 59%
“…46 In particular, the lncRNA H19 (H19) is a key regulator of osteoblast function and is involved in the development of disuse osteoporosis, suggesting that lncRNAs may play a key role in unloading-induced bone loss. 31,32,47,48 Our previous work found many lncRNAs that are significantly differentially expressed in MC3T3-E1 cells under clinorotation unloading condition for 48 h. Further exploration identified a novel unloading-sensitive lncRNA, OGRU, which promotes the osteoblast activity and matrix mineralization and attenuates the osteogenic impairment of MC3T3-E1 cells induced by clinorotation unloading. To further determine whether OGRU can rescue unloading-induced bone loss in vivo, pcDNA3.1(+)-OGRU was delivered via (DSS) 6 -liposomes to bone formation surfaces in HLU mice.…”
Section: Discussionmentioning
confidence: 91%
“…Intersections between various mechanical stimuli and H19 expression have been previously shown, including in a pressure overload model of cardiac hypertrophy, a hindlimb unloading model of osteoporosis, and tension induced osteogenesis. 14,19,30 In these studies, strain correlated with expression of H19. Similarly, H19 is known to be upregulated in calcific aortic valve disease, a pathology characterized by increased valvular strain which augments valve calcification.…”
Section: Discussionmentioning
confidence: 98%
“…Among confirmed osteogenesis‐related lncRNAs, H19 in cell growth and differentiation has been extensively studied. In recent years, several lines of evidence showed its role in the osteogenic differentiation of MSCs (Huang et al, 2015; Li et al, 2017; Liang et al, 2016; Liao et al, 2017). It is noteworthy that lncRNA H19 might involve in the process of osteogenic differentiation of MSCs via Wnt/β‐catenin pathway (Liang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%